2018
DOI: 10.7196/samj.2018.v108i9.13054
|View full text |Cite
|
Sign up to set email alerts
|

The unmet needs and health priorities of the urban poor: Generating the evidence base for urban community health worker programmes in South Africa

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The findings in this review [ 14 , 15 , 18 , 33 ] suggested that performance-based incentives were widely used as an income strategy to motivate and engage CHWs in the delivery of NCD-related health interventions, although the large-scale validity is uncertain. Therefore, future studies and policies need to be concerned about how to expand the coverage of NCMS contract to all village clinics, how to allocate funding and limited resources to better remunerate and motivate CHWs, and how to ensure commitments to human resources development and capacity building [ 6 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings in this review [ 14 , 15 , 18 , 33 ] suggested that performance-based incentives were widely used as an income strategy to motivate and engage CHWs in the delivery of NCD-related health interventions, although the large-scale validity is uncertain. Therefore, future studies and policies need to be concerned about how to expand the coverage of NCMS contract to all village clinics, how to allocate funding and limited resources to better remunerate and motivate CHWs, and how to ensure commitments to human resources development and capacity building [ 6 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the progress achieved with the integration of the CHWs into the formal structure of the ward-based team, there remains ambiguity over the role and scope of CHWs’ tasks as the current ward-based teams are generally top–down, vertical and disease-orientated programmes with challenges arising from poor supervision, inadequate and fragmented disease-specific training. 17,18 Moreover, different interpretation and implementation of the CHW scope, allocated tasks and working conditions are evident in different provinces. 17,18 The National DoH (2015) authorised a rapid assessment of WBOT in seven provinces to understand the challenges and to generate potential solutions.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Moreover, different interpretation and implementation of the CHW scope, allocated tasks and working conditions are evident in different provinces. 17,18 The National DoH (2015) authorised a rapid assessment of WBOT in seven provinces to understand the challenges and to generate potential solutions. 18 The rapid assessments found that WBOT programmes contribute towards maternal and child health, adherence support and home-based care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that investment in the quality of care is highly warranted to reduce barriers that may currently exist in accessing services at PHC facilities. CHWs have been proven to be important to address the unmet need for (health) care in urban communities [20]; in our study, after training, they also managed to mobilise a substantial number of individuals for care of STI-associated symptoms. The traditional structure did not result in the mobilisation of a large number of individuals for care despite the strong role of traditional leaders in these communities [21].…”
Section: Discussionmentioning
confidence: 86%